Transcriptomic Profile Analysis of Streptococcus mutans Response to Acmella paniculata Flower Extracts - Siti Aisyah Abd Ghafar; Nur Syahirah Salehuddin; Nor Zaihana Abdul Rahman; Nadia Halib; Rohazila Mohamad Hanafiah (Hindawi, 2024)
Background. Acmella paniculata has been used as a traditional medicine to treat oral health diseases such as dental caries and periodontitis. Streptococcus mutans is a common bacterium that initiates dental caries at an early stage. Aim. The aim of this study was to determine the mode of action of A. paniculata (extracts) against S. mutans growth. Methods. Time-kill assay has been done to investigate the rate of kill and effectiveness of Acmella paniculata (AP) extracts against S. mutans growth. Phytochemical analysis was done to identify major compounds in AP extracts using gas chromatography mass spectrometry (GCMS). Scanning and transmission electron microscopy (SEM and TEM) have been done to observe the morphological changes of treated bacteria. Transcriptomic profile analysis has been done using Next Gene Sequencing. Results. AP flower n-hexane (APFH) and AP flower dichloromethane (APFD) extracts acted as bactericidal agents after killing >3 log10 cfu/mL of S. mutans after 24 hours. Oleic and hexadecenoic acids were found to be the major compounds in APFD and APFH extracts, respectively. Photomicrographs from SEM and TEM of treated S. mutans show that the bacterial cell wall has been lysed and the cytoplasm content was decreased. Pathway analysis revealed that the APFD extract significantly affected biosynthesis peptidoglycan, gene expression, RNA processing, and macromolecule metabolism processes in S. mutans. Conclusion. Data analysis revealed that multiple mechanisms of action were involved in antibacterial activity of A. paniculata extracts toward S. mutans.